Development of semi-artificial feed in the larva stage of the black soldier fly Hermetia illucens (Diptera: Stratiomyidae) - AURORA DYAS ANASYA; SUGIYARTO SUGIYARTO; EDWI MAHAJOENO (Smujo International, 2022)
Abstract. Anasya AD, Sugiarto, Mahajoeno E. 2022. Development of semi-artificial feed in the larva stage of the black soldier fly Hermetia illucens (Diptera: Stratiomyidae). Nusantara Bioscience 14: 188-194. Alternative food sources in fish farming besides pelleted feed are generally used, but many have also used biotic materials, larvae of the black soldier fly (Hermetia illucens L.). Maggot stadia larvae have a high protein content of more than 19%, could be mass-produced, are low-priced, and has a fast growth time. Therefore, high levels of protein and nutrients in maggots can be increased through suitable semi-artificial formulations. The purpose of this study was to determine the nutritional value of the semi-artificial feed recipe given and to determine the effectiveness of the semi-artificial feed recipe in increasing the nutritional value and survival of larvae. Data analysis used qualitative analysis with descriptive analysis method and quantitative analysis by determining the amount of increased nutritional value of H. illucens. The research method was carried out in several stages, including (i) insect rearing obtained 2nd generation of tillers (F2); (ii) manufacture of semi-artificial feed recipes; (iii) calculation of insect survival; (iv) measurement of larval mass weight after treatment; (v) testing of nutritional content value includes water content, fat content and protein content of H. illucens after treatment. Results of the evaluation larval survival after treatment were effective enough 100%, larval instar life phase was between 28-32 days, while the highest increase in the nutritional value of larvae water content was 45.90%, fat content 7.25%, and protein content 45.95%, the average increase in mass weight of larvae was 12.50%.